Sistema de realidad virtual para el entrenamiento interactivo de dotación e infraestructura del servicio UCI adultos para el personal en ingeniería clínica (2021)
In the absence of training for biomedical engineers regarding regulations, this project was developed, which is part of the development of a virtual reality system for training the engineering skills of the biomedical engineers in a hospital service. For investigation purposes, an accredited hospital with an adults ICU was selected as a model; this entity has compliance with the standards given by resolution 3100 of 2019 as to infrastructure and endowment component, which are part of the unique habilitation system. The application has the medical equipment required and is distributed in an infrastructure with their respective physical characteristics, their functions and implementations. The user will be able to interact and be trained in these standards. The technological development allows the immersion of the user in a virtual reality environment created from the official plans of an intensive care unit, the above guarantees the veracity of the environment and therefore improves the experience, learning and interactivity between the user and the program.